Industrial facilities nonprocess energy. Issue 23 (2nd December 2017) - Bawaneh, Khaled; Overcash, Michael; Twomey, Janet
ABSTRACT: In this study, published information on nonprocess energy use, which includes lighting, heating, cooling, ventilation, humidity control, and particulate control, for industrial buildings has been analyzed and compiled and then represented in power intensity (W/ft 2 ). More than thirty different sources of data related to industrial building energy use (covering about 82 buildings) were identified and analyzed. Energy receives a lot of consideration in analyzing prospective savings in industrial facilities since the industrial sector consumes more than 30% of the total energy in the US. The main objective of this study is to establish representative ranges for nonprocess energy use that can then be used with full process the life cycle for industrial products. The industrial manufacturing buildings were classified into six categories according to nonprocess energy use. The power intensity for each building category was estimated from the available data. Previous analyses of industrial energy use often expressed nonprocess energy as a percentage of total energy but without clear values of actual nonprocess energy. This information is a low value since the actual nonprocess energy is then dominated by the dominator which is unspecified.